Comparison of PRF and toluene/n-heptane mixture in the mechanism of compression ignition using transient species measurements and simplified model analysis - Mohd Adnin, Hamidi (2013)
A heat engine is known as a mechanical system that uses thermal energy came from combustion and changes it into mechanical energy. An easy definition is that, a heat engine changes thermal energy into mechanical energy that can help us in daily life. A heat engine can be defined as external combustion engines and internal combustion engines by the method of heating the working fluid. An internal combustion engine gets the energy directly using heat energy generated by the combustion in the interior of the working fluid. On the other hand, an external heat engine is a heat engine where an (internal) working fluid is heated by combustion in an external source, through the engine wall or a heat exchanger. The fluid then, by expanding and acting on the mechanism of the engine, produces motion and usable work. The fluid is then cooled, compressed and reused (closed cycle), or (less commonly) dumped, and cool fluid pulled in (open cycle air engine).